THE CONCEPTUAL EVOLUTION OF CRISIS COMMUNICATION IN THE AVIATION INDUSTRY: FROM THE THREAT PARADIGM TO THE OPPORTUNITY PARADIGM - Mădălina-Maria TOMA (International Journal of Social and Educational Innovation, 2025)
Crisis communication scholarship has increasingly shifted from viewing crises solely as threats (Birkland, 1968; Fearn-Banks, 1996; Seeger at al., 1998; Pearson & Clair, 1998; Heath & Millar, 2004) to organizational well-being toward recognizing them as potential opportunities for learning and renewal (Coombs, 2019; Diers-Lawson, 2019; Covello, 2022). This theoretical article traces the evolution of crisis communication paradigms, with a focus on the aviation industry as a high-stakes context frequently beset by crises. Early models, such as Corporate Apologia (Hearit, 2006), Image Repair Theory (Benoit, 1995, 1997, 2008) and Situational Crisis Communication Theory (SCCT) (Coombs, 1995, 1999, 2006, 2019), conceptualized crises primarily as reputation threats to be mitigated through defensive messaging​. Newer approaches, including the Discourse of  Renewal (Ulmer, 2007) and the Rhetorical Arena Theory (Frandsen & Johansen, 2010, 2017), reframe crises as catalysts for positive change, emphasizing stakeholder engagement, ethical communication, and organizational growth​. By integrating key theories (SCCT, Image Repair, Arena theory, etc.) and illustrating their application to airline companies (e.g. TAROM, Wizz Air, Blue Air), the paper elucidates how the “threat paradigm” is being supplanted by an “opportunity paradigm” in crisis communication thinking. A summary table of major crisis communication theories is provided, aligning each with either a threat-centric or opportunity-centric perspective in the aviation context. The article concludes that airline organizations can benefit from adopting a renewal-oriented mindset, which not only mitigates damage but also strengthens trust and resilience in the aftermath of crises.